Threshold Concepts in Object-Oriented Modelling - Sien, Ven; Chong, David (Electronic Communications of the EASST, 2012)
Proponents of the object-oriented (OO) paradigm frequently claim that the OO paradigm is ‘more natural’ than the procedural paradigm because the world is filled with objects that have both attributes and behaviors. However students in higher education generally experience considerable difficulty in understanding OO concepts and acquiring the necessary skills in object-oriented analysis and design. This paper proposes OO modelling to be a set of threshold concepts and describes a study that sought to improve undergraduate students’ learning of OO modelling by adopting concept maps as ‘stepping stones’ to facilitate the development of analysis class and sequence diagrams.